480
To get this answer you simply multiply 4.8 by 100
Answer:
45
Step-by-step explanation:
Two tangents drawn to a circle from an outside point form arcs and an angle, and this formula shows the relation between the angle and the two arcs.
m<EYL = (1/2)(m(arc)EVL - m(arc)EHL) Eq. 1
The sum of the angle measures of the two arcs is the angle measure of the entire circle, 360 deg.
m(arc)EVL + m(arc)EHL = 360
m(arc)EVL = 360 - m(arc)EHL Eq. 2
We are given this:
m<EYL = (1/3)m(arc)EHL Eq. 3
Substitute equations 2 and 3 into equation 1.
(1/3)m(arc)EHL = (1/2)[(360 - m(arc)EHL) - m(arc)EHL]
Now we have a single unknown, m(arc)EHL, so we solve for it.
2m(arc)EHL = 3[360 - m(arc)EHL - m(arc)EHL]
2m(arc)EHL = 1080 - 6m(arc)EHL
8m(arc)EHL = 1080
m(arc)EHL = 135
Substitute the arc measure just found in Equation 3.
m<EYL = (1/3)m(arc)EHL
m<EYL = (1/3)(135)
m<EYL = 45
16 n^2 -10n + 129 = 8n^2 -8
We collect the terms:
8n^2 -10n + 137 = 0
The steps for completing the square:
1) Move the "non X" (or "non N") term to the right:
8n^2 -10n = -137
<span>2)<span> Divide the equation by the coefficient of N² which in this case is 8
n^2 -1.2n = </span></span><span><span>-17.125
</span>
3) Take the coefficient of "N"; divide it by 2; square it; add it to both sides of the equation.
-1.2 / 2 = -.6
-.6^2 = .36
</span>
n^2 -1.2n +.36 = <span>-17.125
+.36
Take the square root of both sides:</span>
(n-.6)*(n-.6) = sq root(
<span>
<span>
<span>
-16.765
</span>
</span>
</span>
)
That's about as far as I can go.
Y-(-2)= -2/3(x-6)
3y+6= -2x +12
2x +3y +6=0
You can draw two quarters, a dime, a nickel, and three pennies. Or 6 dimes and 8 pennies.